Hereditární feochromocytom a paragangliom - Musil, Z; Vícha, A; Zelinka, T; Turková, H; Labudová, T; Kohoutová, M; Pacák, K (Klinicka onkologie, 2012)
Pheochromocytomas and paragangliomas are tumors arising from chromaffin cells. These tumors produce catecholamines and are typically found with symptoms and signs that may include hypertension (persistent or episodic), palpitations, headache and sweating. So far, 10 different genes have been associated with both tumors and other genes are expected to be detected. Pheochromocytoma and paraganglioma can occur as a part of genetic syndromes - familial paragangliomas (SDH genes, SDHAF2 gene), von Hippel-Lindau syndrome (VHL gene), multiple endocrine neoplasia type 2 (RET gene), and neurofibromatosis type 1 (NF1 gene). These tumors may be the first and only manifestation of these genetic syndromes. Patients with SDHB mutations are at high risk to develop malignant disease and unfortunately current therapeutic options for malignant form of disease are poor. Genetic testing plays a key role in the management of these tumors and therefore not only index patients with pheochromocytoma but also relatives should be tested. Management of this disease requires multidisciplinary cooperation and should be performed in the specialized medical centres.
Keywords: Heterozygote; Paraganglioma; genetické testování; heterozygot; Genetic Testing; dědičné nádorové syndromy; Humans; paragangliom; lidé; Pheochromocytoma; feochromocytom; Neoplastic Syndromes, Hereditary